(untitled) (Academia Journal of Medicine, 2020)
Background: The stress response that occurs after the event of acute stroke causes the activation of the hypothalamo–pituitary–adrenal (HPA) axis. Certain studies have found that increased serum cortisol level in patients with acute stroke is related to larger infarct volume, greater stroke severity and poor outcome, including death. Subjects and Methods: About 50 new cases of acute ischemic stroke patients, within 72 hours of the acute neurological event , who were admitted in the Sridevi Medical College & Hospital were included in the study. The study was conducted for a period of 6 months.(June 2018-December 2018). CT Brain was taken during admission to confirm acute ischemic stroke. NIHSS (National Institute of Health Stroke Scale)score for all the patients were assessed for severity at the time of admission. Results: Of the 50 cases, serum cortisol level of 23 cases were within normal limits(</=690nmol/L) of which 65.2% had NIHSS score of less than or equal to 6 and 34.8% of the cases had NIHSS score more than 6. Conclusion: Among the patients with acute ischemic stroke ,high serum cortisol levels at the time of admission correlates with,1. Clinical severity which is assessed by National Institute of Health Stroke Scale and 2, Poor prognosis and functional outcome after 15 days which is assessed by Modified Rankin Scale.